(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
This retrospective study is based on the assessment of outcomes of Cochlear Implantation (CI) basing on various scoring systems like Category of Auditory Performance (CAP) and Speech Intelligibility Rating (SIR). 50 candidates, 45 of them who were implanted at CMH Dhaka, a tertiary referral center for cochlear implantation and 05 were implanted outsides (home and Abroad) between June 2012- January 2015 included in the study. The results were analyzed using the above scoring systems to assess the performance levels of each implantee and to arrive at a cumulative result on the outcome of the implantation. Practical issues of concern to Cochlear Implantation in Bangladesh was also analyzed. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 71-77